INCLUSIVE FINANCE AS A POVERTY REDUCTION STRATEGY - Amaniar, Tiara Rizki; Akbar, Wahyu; Ardiansyah, Mawar (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Inclusive finance is a concept that emphasizes the importance of participation from all levels of society in the economic development process. Financial inclusion is believed to be one way to reduce poverty. The aim of this research is to examine more deeply poverty alleviation strategies based on the principles of inclusive economic development in Indonesia. This research uses a qualitative approach with data collection methods based on library research. The data source in this research is a secondary data source. The data analysis method uses qualitative descriptive analysis. Financial inclusion plays an important role in reducing poverty by expanding people's access to formal financial services such as banking, credit and insurance, as well as empowering the community's economy and improving social welfare. However, challenges such as low income, lack of financial infrastructure, and low financial literacy still need to be overcome through the development of affordable financial products, adoption of financial technology (fintech), more intensive financial education programs, as well as support from government regulations and policies, so that financial inclusion can be achieved. more effective in reducing poverty and improving the welfare of society as a whole